Validation of the quality of ultrasound imaging and competence (QUICk) score as an objective assessment tool for the FAST examination. Issue 5 (May 2015) - Ziesmann, Markus Tyler; Park, Jason; Unger, Bertram J.; Kirkpatrick, Andrew W.; Vergis, Ashley; Logsetty, Sarvesh; Pham, Chau; Kirschner, David; Gillman, Lawrence M.
Abstract : BACKGROUND: The Focused Assessment with Sonography for Trauma (FAST) examination has become a valuable tool in trauma resuscitation. Despite the widespread use of FAST training among traumatologists, no evidence-based guidelines exist to support optimal training requirements or to provide quantitative objective assessments of imaging capabilities. Both Task-Specific Checklist (TSC) and Global Rating Scale (GRS) have been validated as objective skill assessment tools; we developed both types of scoring checklist and assessed them for construct validity with the FAST examination. METHODS: Two scoring checklists, collectively termed the Quality of Ultrasound Imaging and Competence (QUICk) Score, were developed and subjected to a modified Delphi consensus process. Two cohorts of 12 novice and 12 expert sonographers performed the FAST examination and were evaluated by two experts according to the QUICk model. Total scores as well as anatomic subsets were compared via comparison of means, and logistic regression modeling was used to determine sensitivity and specificity. RESULTS: Experts achieved significantly higher total scores than novices on both scoring systems (17.2 vs. 11.1 of 24, p < 0.01 TSC, 29.8 vs. 18.4 of 40, p < 0.01 GRS). Sensitivity (85.7% TSC, 92.9% GRS) and specificity (75.0% TSC, 91.7% GRS) as well as area under the receiver operating characteristic curve (89.9% TSC, 97.6% GRS) were consistent with a highly discriminant tool. CONCLUSION: The QUICk Score is the first validated objective tool for assessment of the quality of FAST examination imaging. Use of this tool may be instrumental in developing an evidence-based minimum-performance standard and for assessing quality-improvement modifications in FAST examination training.